2006
DOI: 10.1038/sj.emboj.7601390
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of fission yeast DNA replication origins

Abstract: Eukaryotic DNA replication is initiated from multiple origins of replication, but little is known about the global regulation of origins throughout the genome or in different types of cell cycles. Here, we identify 401 strong origins and 503 putative weaker origins spaced in total every 14 kb throughout the genome of the fission yeast Schizosaccharomyces pombe. The same origins are used during premeiotic and mitotic S-phases. We found that few origins fire late in mitotic S-phase and that activating the Rad3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
362
3
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(402 citation statements)
references
References 43 publications
27
362
3
10
Order By: Relevance
“…In this organism, there is experimental support for a stochastic mode of origin activation provided at the single cell level (27). High-throughput analyses have permitted the location of the majority of putative origins to be specified along the genome (23)(24)(25). Additionally, the firing propensity of each origin along the genome has been determined based on the experimentally defined observed efficiencies in the presence of the drug hydroxyurea, which inhibits fork progression, thereby eliminating passive replication (24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this organism, there is experimental support for a stochastic mode of origin activation provided at the single cell level (27). High-throughput analyses have permitted the location of the majority of putative origins to be specified along the genome (23)(24)(25). Additionally, the firing propensity of each origin along the genome has been determined based on the experimentally defined observed efficiencies in the presence of the drug hydroxyurea, which inhibits fork progression, thereby eliminating passive replication (24).…”
Section: Resultsmentioning
confidence: 99%
“…In this organism, similar to Metazoan cells, replication initiates from specific regions, and no origin defining consensus sequences have been characterized (20). Following publication of the S. pombe genome (21), bioinformatics (22) and highthroughput analyses (23)(24)(25) made it possible to map origins of replication along the complete genome. Dai et al (26) provided evidence that approximately half of the 5.000 intergenic regions present in the S. pombe genome may exhibit origin activity and suggested that the origins active in any given S-phase are recruited stochastically among these intergenic regions.…”
mentioning
confidence: 99%
“…Further evidence for this poor overlap is that the average A þT composition of the 2973 NDRs in the genome (Table I) is 63.4%, which is well below the 70% average A þT composition of all IGRs, and much lower than the A þT content required to specify ORIs in the genome (Segurado et al, 2003;Heichinger et al, 2006;Hayashi et al, 2007;Cotobal et al, 2010). It is conceivable that the unique structure of the Orc4 protein could compensate for the need for NDRs like those described in this work to facilitate access to DNA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent whole-genome analysis using HU revealed an S phase checkpoint in budding yeast that suppresses many origins characterized as late (Feng et al 2006;Raveendranathan et al 2006). However, only a few origins fire late during S phase, and the Rad3-dependent S phase checkpoint has little effect on which origins are fired in fission yeast (Hayashi et al 2007;Heichinger et al 2006). Thus, the physiological significance of temporal regulation of origin firing in fission yeast remains somewhat unclear.…”
Section: Discussionmentioning
confidence: 99%